The Impact of COVID-19 on Birth Weight during Pregnancy - Arien Dwi Ajeng Adhe Safitri; Isnin Anang Marhana; Budi Prasetyo; Dominicus Husada; Erni Rosita Dewi (Jurnal Respirasi, 2023)
Introduction: Coronavirus is a viral pathogen that can be transmitted through respiratory droplets, leading to severe infectious diseases. This study aimed to ascertain the influence of the COVID-19 pandemic on birth weight during pregnancy. Methods: This study used secondary data and a retrospective case-control approach for observational analysis. The case and control groups each had 153 samples. The case group was further separated into symptomatic and asymptomatic categories. Statistical analyses were performed to determine how COVID-19 infection in pregnant women affected birth weight. Fisher's exact test was used to evaluate data for the subgroups of asymptomatic and symptomatic individuals, while the Mann-Whitney test was used to compare the infection's impact. Results: Most participants were 21–35 years old (78.2%). The findings showed that 85% of pregnant COVID-19 patients were in their third trimester. Mothers diagnosed with COVID-19 had infants with birth weights of >4,000 grams (3.3%), 2,500–4,000 grams (43.1%), and <2,500 grams (53.6%). Birth weight distribution in women unaffected by COVID-19 was >4,000 grams (14.4%), 2,500–4,000 grams (67.3%), and <2,500 grams (18.3%). The Mann-Whitney statistical test was performed using SPSS. It yielded a p-value of 0.001, less than the significance level of 0.05, indicating a correlation between confirmed COVID-19 infection in pregnant women and birth weight. Conclusion: This study found that the presence of COVID-19 infection during pregnancy significantly affects infants' birth weight.